Flame-retardant self-repairing water-based paint and preparation method thereof
By introducing flame retardant self-healing fillers with core-shell structure into the flame retardant coating, the self-repair of the coating is achieved by using photocatalytic and thermal activation technologies, the problem of failure of existing flame retardant coatings after damage is solved, efficient heat insulation and smoke resistance are achieved, and suitable for assembly line production.
Patent Information
- Application Number
- CN202411850175.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-16
AI Technical Summary
Existing flame retardant coatings fail after the paint is damaged, making it impossible to achieve effective thermal insulation protection and smoke protection, and cannot meet the needs of assembly line production.
Flame-retardant self-healing filler with core-shell structure is used, with styrene as the shell, polyimide aerogel as the core, nanotitanium dioxide particles are loaded on the styrene shell, and aerodry alkyd resin is adsorbed in the polyimide aerogel. When the coating is damaged, the filler is activated by ultraviolet irradiation or heated by a hot air fan to achieve self-healing of the coating.
The coating is successfully repaired repeatedly, maintains flame retardant performance and thermal insulation, extends the coating's use time, and reduces the generation of toxic flue gases.
Smart Images

Figure BDA0005190362880000021 
Figure BDA0005190362880000051 
Figure BDA0005190362880000091
Abstract
Description
Technical Field The invention relates to the field of architectural coatings, and in particular to a flame retardant self-repairing water-based coating and a preparation method thereof. Background Art At present, the use of coatings is closely related to interfaces. Coatings are a multi-component system, including resins (base materials), pigments, fillers, solvents and additives. There are many interfaces within the system, especially between pigments, fillers, resins and solvents. At the same time, coatings are semi-finished products that must be applied to workpieces, products, and structures to provide protection, decoration, and functions. Therefore, there must be a certain interface state, which also puts forward certain requirements for the use of coatings. In addition, after the coating is applied, there is a drying and curing process, which must take into account the contact between the coating (wet) surface and the air to ensure that a good coating appearance can be provided and prevent the occurrence of surface defects. Wood products themselves are prone to fire due to their low ignition point and flammable properties. To avoid this problem, the current method is mainly to add flame retardant liquid or apply flame retardant coatings to wood. However, existing flame retardant coatings cannot effectively insulate wood products, nor do they have smoke-proof effects. Some flame retardant materials even release toxic halogen-containing gases when they decompose. In addition, if the coating of building materials coated with flame retardant coatings is damaged during use, peeling will make the flame retardant effect ineffective. At the same time, existing flame retardant coatings cannot meet the production needs of the assembly line. Therefore, in order to ensure and improve the flame retardant and repair effects of the coating film so that it can have a longer service life, the existing technology must be improved. Summary of the invention
[0003] Technical problem to be solved: The present invention aims to solve the technical problem that the flame retardant effect will be ineffective if the paint of building materials is damaged during use and peeling off causes the flame retardant effect to be ineffective. A flame retardant self-repairing filler with a core-shell structure is added, with styrene as the shell and polyimide aerogel as the core; nano-titanium dioxide particles are loaded on the styrene shell, and air-drying alkyd resin is adsorbed in the polyimide aerogel. When the coating is scratched or damaged for the first time, ultraviolet irradiation is used to photocatalyze the nano-titanium dioxide on the styrene shell to catalyze and degrade the styrene shell, causing it to rupture and release the air-drying alkyd resin, which reacts with the air to form a film, and the damaged part is repaired in time, so that the ruptured part of the coating will not continue to extend; when the coating is scratched or damaged for the second or third time, a hot air blower is used to heat the polyimide aerogel, the adsorption amount of the air-drying alkyd resin decreases, the air-drying alkyd resin overflows, and the coating continues to be repaired, thereby achieving a sustainable multiple repair effect of the coating.
[0004] Technical solution: A flame-retardant self-repairing water-based coating, prepared from polyurethane emulsion and a core-shell structured flame-retardant self-repairing filler; The flame-retardant self-repairing filler with a core-shell structure has styrene as a shell and polyimide aerogel as a core; nano-titanium dioxide particles are loaded on the styrene shell, and air-drying alkyd resin is adsorbed in the polyimide aerogel. Furthermore, the particle size of the flame retardant self-repairing filler of the core-shell structure is 1-20 μm. Furthermore, the adsorption amount of the polyimide aerogel on the air-drying alkyd resin decreases with increasing temperature. Furthermore, the flame retardant self-repairing water-based coating is composed of the following components in percentage by weight: The polyurethane emulsion is an organosilicon-modified polyurethane emulsion. Furthermore, the preparation steps of the core-shell structured flame retardant self-repairing filler are as follows: S1: Add 10 mL of thionyl chloride to 1.28 g of polyimide containing carboxylic acid side groups, reflux for 0.5 h, reduce pressure and gradually increase the temperature to 150 ° C; add 0.18 g of aminopropyl-terminated polydimethylsiloxane, 0.32 g of aminopropyltrimethoxysilane, 0.20 g of triethylamine, 15 mL of N, N-dimethylformamide and 15 mL of tetrahydrofuran, stir and react for 30 min, centrifuge to obtain a solution; S2: Add 0.16 g water, 0.015 g HCl, 7.5 mL N, N-dimethylformamide and 7.5 mL tetrahydrofuran to the solution, stir rapidly for 3 min and let stand for 3 d, take out the formed gel, replace it twice with a mixed solvent of N, N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1, and then replace it with tert-butanol for 4 times; S3: freezing at -25°C, drying with a freeze dryer, and crushing to obtain a polyimide aerogel; S4: immersing the polyimide aerogel in an air-drying alkyd resin for adsorption to saturation; S5: taking out and drying at a low temperature of 20-30° C. to obtain a polyimide aerogel adsorbing an air-drying alkyd resin; S6: 800 g of styrene monomer and 6 g of azobisisobutyronitrile are mixed, ultrasonically stirred to dissolve, 50-100 g of nano titanium dioxide is added, and stirred evenly to obtain a mixed dispersion containing nano titanium dioxide; S7: The polyimide aerogel adsorbed with air-drying alkyd resin is immersed in a mixed dispersion containing nano-titanium dioxide, sealed, and reacted at 70°C for 18 hours and at 80°C for 18 hours in a vacuum drying oven to obtain a flame-retardant self-healing filler with a core-shell structure. Furthermore, the mass volume ratio of the polyimide aerogel adsorbed with air-drying alkyd resin and the mixed dispersion containing nano-titanium dioxide in S7 is 20g:(3-5)mL. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Apply the flame retardant self-repairing water-based coating on the surface of the wood product; Step 2: Curing with a hot air blower; Step 3: Finished product packaging on the assembly line. Furthermore, the coating method includes roller coating, electrostatic spraying, vacuum spraying, shower coating, dip coating, spin coating and pump coating. Furthermore, in step 2, the curing temperature is 50-60° C. and the curing time is 30-40 seconds. Beneficial effects: 1. The flame-retardant self-repairing water-based coating of the present invention is prepared by using a flame-retardant self-repairing filler with a core-shell structure, with styrene as the shell and polyimide aerogel as the core; nano-titanium dioxide particles are loaded on the styrene shell, and air-drying alkyd resin is adsorbed in the polyimide aerogel. When the coating is scratched or damaged for the first time, ultraviolet irradiation is used to photocatalyze the nano-titanium dioxide on the styrene shell to catalyze and degrade the styrene shell, causing it to rupture and release the air-drying alkyd resin, which reacts with the air to form a film, and the damaged part is repaired in time, so that the ruptured part of the coating will not continue to extend; when the coating is scratched or damaged for the second or third time, a hot air blower is used to heat the polyimide aerogel, thereby increasing the temperature of the polyimide aerogel, reducing the adsorption of the air-drying alkyd resin, causing the air-drying alkyd resin to overflow, and continuing to repair the coating, thereby achieving a sustainable multiple repair effect of the coating. 2. The present invention adopts a flame-retardant self-repairing filler with a core-shell structure, and coats styrene on the outer layer of the polyimide aerogel adsorbed with the air-drying alkyd resin, so as to achieve initial protection for the polyimide aerogel and prevent the air-drying alkyd resin in the polyimide aerogel from overflowing during the curing process of the coating using a hot air blower. 3. When the present invention encounters fire and burns, as the temperature rises, the polyimide aerogel melts to form a fluid, forms an interpenetrating network with the organosilicon-modified polyurethane, and finally forms a dense carbon layer, thereby improving the flame retardant performance; at the same time, the nano-titanium dioxide particles on the styrene shell can enter the holes in the carbon layer, further isolating the air, and promoting the organosilicon-modified polyurethane to produce a denser carbon layer, thereby reducing the toxic smoke generated by combustion. 4. The flame-retardant self-repairing water-based coating of the present invention uses polyimide aerogel, which has good thermal insulation effect, can delay or prevent the spread of fire, block heat conduction, and increase the thermal insulation effect. DETAILED DESCRIPTION Example 1 The preparation steps of a flame retardant self-repairing filler with a core-shell structure are as follows: S1: Add 1 L of thionyl chloride to 128 g of polyimide containing carboxylic acid side groups, reflux for 0.5 h, reduce pressure and gradually increase the temperature to 150 ° C; add 18 g of aminopropyl-terminated polydimethylsiloxane, 32 g of aminopropyltrimethoxysilane, 20 g of triethylamine, 1.5 L of N, N-dimethylformamide and 1.5 L of tetrahydrofuran, stir and react for 30 min, centrifuge to obtain a solution; S2: Add 16 mL of water, 1.5 g of HCl, 750 mL of N,N-dimethylformamide and 750 mL of tetrahydrofuran to the solution, stir rapidly for 3 min and then let stand for 3 d. Take out the formed gel and replace it twice with a mixed solvent of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1, and then replace it with tert-butanol for 4 times; S3: freezing at -25°C, drying with a freeze dryer, and crushing to obtain a polyimide aerogel; S4: immersing the polyimide aerogel in an air-drying alkyd resin for adsorption to saturation; S5: taking out and low-temperature drying at 25° C. to obtain a polyimide aerogel adsorbing an air-drying alkyd resin; S6: 800 g of styrene monomer and 6 g of azobisisobutyronitrile were mixed, ultrasonically stirred to dissolve, 50 g of nano titanium dioxide was added, and stirred evenly to obtain a mixed dispersion containing nano titanium dioxide; S7: 20 g of polyimide aerogel adsorbed with air-drying alkyd resin was immersed in 4 mL of mixed dispersion containing nano-titanium dioxide, sealed, and reacted at 70° C. for 18 h and at 80° C. for 18 h in a vacuum drying oven to obtain a flame-retardant self-healing filler with a core-shell structure. Example 2 The preparation steps of a flame retardant self-repairing filler with a core-shell structure are as follows: S1: Add 1 L of thionyl chloride to 128 g of polyimide containing carboxylic acid side groups, reflux for 0.5 h, reduce pressure and gradually increase the temperature to 150 ° C; add 18 g of aminopropyl-terminated polydimethylsiloxane, 32 g of aminopropyltrimethoxysilane, 20 g of triethylamine, 1.5 L of N, N-dimethylformamide and 1.5 L of tetrahydrofuran, stir and react for 30 min, centrifuge to obtain a solution; S2: Add 16 mL of water, 1.5 g of HCl, 750 mL of N,N-dimethylformamide and 750 mL of tetrahydrofuran to the solution, stir rapidly for 3 min and then let stand for 3 d. Take out the formed gel and replace it twice with a mixed solvent of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1, and then replace it with tert-butanol for 4 times; S3: freezing at -25°C, drying with a freeze dryer, and crushing to obtain a polyimide aerogel; S4: immersing the polyimide aerogel in an air-drying alkyd resin for adsorption to saturation; S5: taking out and low-temperature drying at 25° C. to obtain a polyimide aerogel adsorbing an air-drying alkyd resin; S6: 800 g of styrene monomer and 6 g of azobisisobutyronitrile were mixed, ultrasonically stirred to dissolve, 80 g of nano titanium dioxide was added, and stirred evenly to obtain a mixed dispersion containing nano titanium dioxide; S7: 20 g of polyimide aerogel adsorbed with air-drying alkyd resin was immersed in 4 mL of mixed dispersion containing nano-titanium dioxide, sealed, and reacted at 70° C. for 18 h and at 80° C. for 18 h in a vacuum drying oven to obtain a flame-retardant self-healing filler with a core-shell structure. Example 3 The preparation steps of a flame retardant self-repairing filler with a core-shell structure are as follows: S1: Add 1 L of thionyl chloride to 128 g of polyimide containing carboxylic acid side groups, reflux for 0.5 h, reduce pressure and gradually increase the temperature to 150 ° C; add 18 g of aminopropyl-terminated polydimethylsiloxane, 32 g of aminopropyltrimethoxysilane, 20 g of triethylamine, 1.5 L of N, N-dimethylformamide and 1.5 L of tetrahydrofuran, stir and react for 30 min, centrifuge to obtain a solution; S2: Add 16 mL of water, 1.5 g of HCl, 750 mL of N,N-dimethylformamide and 750 mL of tetrahydrofuran to the solution, stir rapidly for 3 min and then let stand for 3 d. Take out the formed gel and replace it twice with a mixed solvent of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1, and then replace it with tert-butanol for 4 times; S3: freezing at -25°C, drying with a freeze dryer, and crushing to obtain a polyimide aerogel; S4: immersing the polyimide aerogel in an air-drying alkyd resin for adsorption to saturation; S5: taking out and low-temperature drying at 25° C. to obtain a polyimide aerogel adsorbing an air-drying alkyd resin; S6: 800 g of styrene monomer and 6 g of azobisisobutyronitrile were mixed, ultrasonically stirred to dissolve, 100 g of nano-titanium dioxide was added, and stirred evenly to obtain a mixed dispersion containing nano-titanium dioxide; S7: 20 g of polyimide aerogel adsorbed with air-drying alkyd resin was immersed in 4 mL of mixed dispersion containing nano-titanium dioxide, sealed, and reacted at 70° C. for 18 h and at 80° C. for 18 h in a vacuum drying oven to obtain a flame-retardant self-healing filler with a core-shell structure. Comparative Example 1 The difference between this embodiment and embodiment 2 is that the polyimide aerogel is not subjected to hydrophobic modification, as follows: The preparation steps of a flame retardant self-repairing filler with a core-shell structure are as follows: S1: Add 1 L of thionyl chloride to 128 g of polyimide containing carboxylic acid side groups, reflux for 0.5 h, reduce the pressure and gradually increase the temperature to 150° C.; add 20 g of triethylamine, 1.5 L of N,N-dimethylformamide and 1.5 L of tetrahydrofuran, stir and react for 30 min, centrifuge to obtain a solution; S2: Add 16 mL of water, 1.5 g of HCl, 750 mL of N,N-dimethylformamide and 750 mL of tetrahydrofuran to the solution, stir rapidly for 3 min and then let stand for 3 d. Take out the formed gel and replace it twice with a mixed solvent of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1, and then replace it with tert-butanol for 4 times; S3: freezing at -25°C, drying with a freeze dryer, and crushing to obtain a polyimide aerogel; S4: immersing the polyimide aerogel in an air-drying alkyd resin for adsorption to saturation; S5: taking out and low-temperature drying at 25° C. to obtain a polyimide aerogel adsorbing an air-drying alkyd resin; S6: 800 g of styrene monomer and 6 g of azobisisobutyronitrile were mixed, ultrasonically stirred to dissolve, 80 g of nano titanium dioxide was added, and stirred evenly to obtain a mixed dispersion containing nano titanium dioxide; S7: 20 g of polyimide aerogel adsorbed with air-drying alkyd resin was immersed in 4 mL of mixed dispersion containing nano-titanium dioxide, sealed, and reacted at 70° C. for 18 h and at 80° C. for 18 h in a vacuum drying oven to obtain a flame-retardant self-healing filler with a core-shell structure. The adsorption amount of the polyimide aerogel for the air-drying alkyd resin in Example 2 was measured at different temperatures. The results are shown in Table 1: Table 1 It can be seen from Table 1 that the adsorption amount of air-drying alkyd resin by polyimide aerogel decreases with increasing temperature, which means that the air-drying alkyd resin can overflow from the polyimide aerogel by high-temperature heating. Example 4 A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 20% of a flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Example 2, 8% of BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; All ingredients are mixed and stirred to obtain a self-healing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 150 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Example 5 A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 25% of a flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Example 2, 8% of a dispersant BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; All ingredients are mixed and stirred to obtain a self-healing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 150 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Example 6 A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 30% of a flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Example 2, 8% of a dispersant BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; All ingredients are mixed and stirred to obtain a self-healing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 150 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Example 7 A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 25% of a flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Example 2, 8% of a dispersant BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; All ingredients are mixed and stirred to obtain a self-healing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 100 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Example 8 A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 25% of a flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Example 2, 8% of a dispersant BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; All ingredients are mixed and stirred to obtain a self-healing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 200 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Example 9 A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 25% of a flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Example 1, 8% of a dispersant BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; All ingredients are mixed and stirred to obtain a self-healing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 150 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Example 10 A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 25% of a flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Example 3, 8% of a dispersant BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; All ingredients are mixed and stirred to obtain a self-healing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 150 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Comparative Example 2 The difference between this comparative example and Example 5 is that air-drying alkyd resin self-repairing microcapsules are directly added, as follows: A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 25% of air-drying alkyd resin self-repairing microcapsules, 8% of dispersant BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; The preparation method of air-drying alkyd resin self-repairing microcapsules is as follows: 10g gelatin solution and 20g air-drying alkyd resin are added to a reactor, stirred at a speed of 400r / min and a temperature of 60°C for 90min, 3g sodium sulfate solution is added, and stirring is continued for 30min in an ice-water bath, 3g glutaraldehyde is added, and stirring is continued for 3min, and then standing for 10min, filtered and dried. All the ingredients are mixed and stirred to obtain a self-repairing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 150 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Comparative Example 3 The difference between this comparative example and Example 5 is that the flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Comparative Example 1 is as follows: A flame retardant self-repairing water-based coating, comprising the following components in weight percentage: 50% of organosilicon-modified polyurethane emulsion, 25% of a flame retardant self-repairing filler with a core-shell structure having a particle size of 1-20 μm prepared in Comparative Example 1, 8% of BYK-192 (chemical product of BYK Company), 3% of BYK-022 (chemical product of BYK Company), and the balance of pure water; All ingredients are mixed and stirred to obtain a self-healing flame-retardant water-based coating. The method for using the flame retardant self-repairing water-based coating comprises the following steps: Step 1: Roll the flame retardant self-repairing water-based paint onto the surface of the wood product with a thickness of 150 μm; Step 2: Use a hot air blower to cure, the curing temperature is 50°C, and the curing time is 40s; Step 3: Finished product packaging on the assembly line. Determination of the self-repairing performance of the embodiment of the present invention: Self-repair performance test: First scratch: scratch the coating with a surgical blade, irradiate the scratched coating with ultraviolet light for 10 hours, and observe the wound recovery status with an optical microscope; Second scratch: scratch the coating with a surgical blade, heat the scratched coating to 80°C with a hot air blower, and observe the wound recovery status with an optical microscope after 40 minutes; Third scratch: scratch the coating with a surgical blade, heat the scratched coating to 120°C with a hot air blower, and observe the wound recovery status with an optical microscope after 40 minutes; the results are shown in Table 2 below: Table 2 Determination of the flame retardant properties of the embodiments of the present invention: According to GB / T2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method", the Limiting Oxygen Index (LOI) test is carried out to evaluate the flame retardant properties of the material; According to ISO5660 standard, cone calorimeter was used to test the heat release performance of flame retardant poplar plywood. The sample size was 100mm×100mm×3mm and the radiation intensity was 35kW / m 2 . The results are shown in Table 3 below: Table 3
Claims
1. A flame retardant self-repairing water-based coating, characterized in that: It is prepared from polyurethane emulsion and flame-retardant self-repairing filler with core-shell structure; The flame-retardant self-repairing filler with a core-shell structure has styrene as a shell and polyimide aerogel as a core; nano-titanium dioxide particles are loaded on the styrene shell, and air-drying alkyd resin is adsorbed in the polyimide aerogel.
2. The flame retardant self-repairing water-based coating according to claim 1, characterized in that: The particle size of the flame retardant self-repairing filler of the core-shell structure is 1-20 μm.
3. The flame retardant self-repairing water-based coating according to claim 1, characterized in that: The adsorption amount of the polyimide aerogel on the air-drying alkyd resin decreases with increasing temperature.
4. The flame retardant self-repairing water-based coating according to claim 1, characterized in that: It is composed of the following components in weight percentage: The polyurethane emulsion is an organosilicon-modified polyurethane emulsion.
5. The flame retardant self-repairing water-based coating according to claim 1, characterized in that: The preparation steps of the core-shell structured flame retardant self-repairing filler are as follows: S1: Add 10 mL of thionyl chloride to 1.28 g of polyimide containing carboxylic acid side groups, reflux for 0.5 h, reduce pressure and gradually increase the temperature to 150 ° C; add 0.18 g of aminopropyl-terminated polydimethylsiloxane, 0.32 g of aminopropyltrimethoxysilane, 0.20 g of triethylamine, 15 mL of N, N-dimethylformamide and 15 mL of tetrahydrofuran, stir and react for 30 min, centrifuge to obtain a solution; S2: Add 0.16 g water, 0.015 g HCl, 7.5 mL N, N-dimethylformamide and 7.5 mL tetrahydrofuran to the solution, stir rapidly for 3 min and let stand for 3 d, take out the formed gel, replace it twice with a mixed solvent of N, N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1, and then replace it with tert-butanol for 4 times; S3: freezing at -25°C, drying with a freeze dryer, and crushing to obtain a polyimide aerogel; S4: immersing the polyimide aerogel in an air-drying alkyd resin for adsorption to saturation; S5: taking out and drying at a low temperature of 20-30° C. to obtain a polyimide aerogel adsorbing an air-drying alkyd resin; S6: 800 g of styrene monomer and 6 g of azobisisobutyronitrile are mixed, ultrasonically stirred to dissolve, 50-100 g of nano titanium dioxide is added, and stirred evenly to obtain a mixed dispersion containing nano titanium dioxide; S7: The polyimide aerogel adsorbed with the air-drying alkyd resin is impregnated in a mixed dispersion containing nano-titanium dioxide, sealed, and reacted at 70° C. for 18 h and at 80° C. for 18 h in a vacuum drying oven to obtain a flame-retardant self-healing filler with a core-shell structure.
6. The flame retardant self-repairing water-based coating according to claim 5, characterized in that: The mass volume ratio of the polyimide aerogel adsorbed with air-drying alkyd resin and the mixed dispersion containing nano-titanium dioxide in the S7 is 20 g: (3-5) mL.
7. A method for using a flame retardant self-repairing water-based coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Apply the flame retardant self-repairing water-based coating on the surface of the wood product; Step 2: Curing with a hot air blower; Step 3: Finished product packaging on the assembly line.
8. The method for using the flame retardant self-repairing water-based coating according to claim 6, characterized in that: The coating methods include roller coating, electrostatic spraying, vacuum spraying, shower coating, dip coating, spin coating and pump coating.
9. The method for using a flame retardant self-repairing water-based coating according to claim 6, characterized in that: In step 2, the curing temperature is 50-60° C. and the curing time is 30-40 seconds.
Citation Information
Patent Citations
Microcapsule type additive for corrosion-resistant coating and preparation method thereof
CN104927468A
Self-repairing flame-retardant water-based paint
CN114316656A
Self-repairing scratch-resistant wear-resistant ultraviolet curing coating for plastic products and application of self-repairing scratch-resistant wear-resistant ultraviolet curing coating
CN114316789A
A method for producing microcapsule providing self-healing property to a multi-functional resin coating composition
KR1020150049852A